Resource management in cloud computing: Taxonomy, prospects, and challenges. (October 2015) - Mustafa, Saad; Nazir, Babar; Hayat, Amir; Khan, Atta ur Rehman; Madani, Sajjad A.
Abstract: Cloud computing has emerged as a popular computing paradigm for hosting large computing systems and services. Recently, significant research is carried out on Resource Management (RM) techniques that focus on the efficient sharing of cloud resources among multiple users. RM techniques in cloud are designed for computing and workload intensive applications that have different optimization parameters. This study presents a comprehensive review of RM techniques and elaborates their extensive taxonomy based on the distinct features. It highlights evaluation parameters and platforms that are used to evaluate RM techniques. Moreover, it presents design goals and research challenges that should be considered while proposing novel RM techniques.